(untitled) (The Peerian Journal, 2023)
This article offers suggestions on modern methods of supply chain development, organization of complex organizational and technical facilities, application of logistics engineering principles for efficient infrastructure development, and use of a proactive (warning) method in supply chain development, describes the main directions that determine the efficiency of the railway transport services, the relationship between the concepts of railway transport services, transport system and transport infrastructure and the main factors influencing the choice of mode of transport, suggestions for improvement are given and the volume of transportation of certain types of cargo in railway transport and the volume of investments involved in the activities of JSC "Uzbekistan Railways" were analyzed, the most important conditions for the structural reform of railway transport were indicated , based on the results of the analysis, the studied problems were systematized, and at the same time, the principles of strategic integration of railway transport and the development model of the railway transport system, as well as directions of economic development, which included six stages, were proposed.